CULTURAL FILTERING IN LANGUAGE TRANSLATION - Wati, Atikah (Universitas Wiralodra, 2017)
The aim of this paper is to find out the important of cultural filtering that used by translator in language translation. As we know that language and culture being inextricably interwoven, the transference of the linguistic expression is precisely an attempt to integrate elements of one culture into another. Translation, thus, becomes a cross cultural event and the translator has to formulate his translation strategies to translate source culture into target culture. To deal with these cultural problems, translator is supposed to insert cultural filter in the initial stage of understanding and analyzing codification of the source text in the first stance. Here the cultural filter helps translator in obtain various elements of source culture which cannot go as they are in the target culture because of cultural differences.